The role and interaction between transcription factor NAC‐NOR and DNA demethylase SlDML2 in the biosynthesis of tomato fruit flavor volatiles. Issue 5 (30th June 2022) - Gao, Ying; Lin, Yujing; Xu, Min; Bian, Hanxiao; Zhang, Chi; Wang, Jingyu; Wang, Hanqing; Xu, Yaping; Niu, Qingfeng; Zuo, Jinhua; Fu, Da‐Qi; Pan, Yu; et al.
Summary: Flavor‐imparting volatile chemicals accumulate as fruits ripen, making major contributions to taste. The NAC transcription factor nonripening (NAC‐NOR) and DNA demethylase 2 (SlDML2) are essential for tomato fruit ripening, but details of the potential roles and the relationship between these two regulators in the synthesis of volatiles are lacking. Here, we show substantial reductions in fatty acid and carotenoid‐derived volatiles in tomato slnor and sldml2 mutants. An unexpected finding is the redundancy and divergence in volatile profiles, biosynthetic gene expression, and DNA methylation in slnor and sldml2 mutants relative to wild‐type tomato fruit. Reduced transcript levels are accompanied by hypermethylation of promoters, including the NAC‐NOR target gene lipoxygenase ( SlLOXC ) that is involved in fatty acid‐derived volatile synthesis. Interestingly, NAC‐NOR activates SlDML2 expression by directly binding to its promoter both in vitro and in vivo . Meanwhile, reduced NAC‐NOR expression in the sldml2 mutant is accompanied by hypermethylation of its promoter. These results reveal a relationship between SlDML2‐mediated DNA demethylation and NAC‐NOR during tomato fruit ripening. In addition to providing new insights into the metabolic modulation of flavor volatiles, the outcome of our study contributes to understanding the genetics and control of fruit ripening and quality attributes in tomato.